DPHC From Alpinia officinarum Ameliorates Oxidative Stress and Insulin Resistance via Activation of Nrf2/ARE Pathway in db/db Mice and High Glucose-Treated HepG2 Cells - Zhang, Xuguang; Zhang, Yuxin; Zhou, Mingyan; Xie, Yiqiang; Dong, Xiujuan; Bai, Feihu; Zhang, Junqing (Frontiers in Pharmacology, 2022)
(R)-5-hydroxy-1,7-diphenyl-3-heptanone (DPHC) from the natural plant Alpinia officinarum has been reported to have anti-oxidation and anti-diabetic effects. In this study, the therapeutic effect and molecular mechanism of DPHC on type 2 diabetes mellitus (T2DM) were investigated based on regulation of oxidative stress and insulin resistance (IR) in vivo and in vitro. In vivo, the fasting blood glucose (FBG) level of db/db mice was significantly reduced with improved glucose tolerance and insulin sensitivity after 8 weeks of treatment with DPHC. In vitro, DPHC ameliorated IR because of it increasing glucose consumption and glucose uptake of IR-HepG2 cells induced by high glucose. In addition, in vitro and in vivo experiments showed that DPHC could regulate the antioxidant enzyme levels including superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px), thereby reducing the occurrence of oxidative stress and improving insulin resistance. Western blotting and polymerase chain reaction results showed that DPHC could promote the expressions of nuclear factor erythroid 2-related factor 2 (Nrf2), the heme oxygenase-1 (HO-1), protein kinase B (AKT) and glucose transporter type 4 (GLUT4), and reduced the phosphorylation levels of c-Jun N-terminal kinase (JNK) and insulin receptor substrate-1 (IRS-1) on Ser307 both in vivo and in vitro. These findings verified that DPHC has the potential to relieve oxidative stress and IR to cure T2DM by activating Nrf2/ARE signaling pathway in db/db mice and IR-HepG2 cells.